Повышение единичной мощности и эффективности ВЭУ с аэродинамической мультипликацией - Андриенко, Петр Дмитриевич; Метельский, Владимир Петрович; Немудрый, Игорь Юрьевич (НТУ "ХПИ", 2013)
The article describes ways to increase the unit capacity of wind power plants with aerodynamic multiplication by increasing the frequency inductor generators and the use of frequency converters with high voltage. Saving a unit mass of generators increased plant capacity up to 2 MW or more for high-efficiency.
Keywords: ветроэлектрические установки; частота индукторных генераторов; преобразователи частоты; повышенное напряжение; высокочастотные генераторы; плоскости ветроколеса